2021
DOI: 10.12691/ajmcr-9-3-6
|View full text |Cite
|
Sign up to set email alerts
|

Acute Severe Thrombocytopenia Event Associated with Trimethoprim/Sulfamethoxazole Use

Abstract: Objective: To report a case of life-threatening thrombocytopenia associated with the use of trimethoprim/sulfamethoxazole (TMP/SMX) therapy. Report of the case: 50-year-old woman with no significant past medical history who presented with one day of petechial rash on her arms, chest and legs. Patient reports that she had just completed a 7- day course of TMP/SMX (1-double strength tablet twice a day) for uncomplicated UTI by her PMD. On admission, the patient was hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The present study designed to distribution of the prevalence of the drug induced thrombocytopenia found that the prevalence is 4.7% in selected cities, these findings were similar to the study. [8][9][10][11] the study witnessed that out of 261 samples 165 (63.21%) were males and 96 (58.18%) were females these finding were similar to study [12][13][14][15][16] and the study also found that the age of drug induced thrombocytopenia is similar in all age groups these findings were similar to the study. 17,18…”
Section: Discussionsupporting
confidence: 84%
“…The present study designed to distribution of the prevalence of the drug induced thrombocytopenia found that the prevalence is 4.7% in selected cities, these findings were similar to the study. [8][9][10][11] the study witnessed that out of 261 samples 165 (63.21%) were males and 96 (58.18%) were females these finding were similar to study [12][13][14][15][16] and the study also found that the age of drug induced thrombocytopenia is similar in all age groups these findings were similar to the study. 17,18…”
Section: Discussionsupporting
confidence: 84%
“…DITP is an adverse drug reaction (ADR) and a signi cantly underrecognized clinical problem. In the event of DITP, the platelet count is usually below 100×10 9 /L; therefore, DITP can often lead to abrupt and severe bleeding complications and even death [2,3]. DITP urgently requires further attention since its cumulative incidence is 10 cases per million population per year, with a 25% prevalence in critically ill patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-induced thrombocytopenia (DITP) is an adverse reaction and a significantly under-recognized clinical problem. The platelet count is usually less than 100×10 9 /L; therefore, DITP can often lead to abrupt and severe bleeding complications and even death ( Vayne et al, 2020 ; Doodnauth et al, 2021 ). DITP deserves special attention since its cumulative incidence is 10 cases per million population per year, with a prevalence as high as 25% in critically ill patients ( Danese et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%